LA SENSIBILIDAD DE ERNESTO Ernesto’s sensitivity - Ileana Roca Ferrer (Universidad de Ciencias Médicas de La Habana, 2008)
He was a man in flesh and blood, it was true that he was very demanding with himself, but we have to make an effort to get close to him. Ernesto goes to look for weapons to fight, because of him being followed; he takes asylum in the Argentinean Embassy. If we were about to resume: Che was a man in flesh and blood, with defects as well as virtues, more virtues than defects, but a regular man. He was physically handsome, a good poet, a good doctor a good photographer, sensitive and brave. He was incapable of neither accepting nor saying lies, whenever they come from or to accept anything that didn’t correspond to his position of Minister or Commander. He was always capable of giving an example, that was his worry, that he was very harsh in doing or saying things. That sensitivity must be cultivated; truth and justice must be loved. There are a lot of Che’s to emphasize.